2020
DOI: 10.1016/j.jenvman.2020.110239
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from volume to economic value in virtual water allocation problems: A proposed new framework and methodology

Abstract: The water footprint provided a full methodology to operationalise the virtual water concept (the volume of water used along a supply chain to produce products and services). A key theme in the water footprint literature is the efficient allocation of water resources at the global scale given the feasibility of trading water intensive commodities from water rich to water poor areas: this is an economic problem of resource allocation between alternative and competing demands, albeit with a novel international co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Regarding the fruits, the highest value of 1 m3 was obtained 3997 Tomans from oranges and the lowest value 401 Tomans from olives. Our findings about economic value is similar to Lowe et al (2020). They showed that the total value of the virtual water used to produce one tonne of durum wheat pasta ($212).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the fruits, the highest value of 1 m3 was obtained 3997 Tomans from oranges and the lowest value 401 Tomans from olives. Our findings about economic value is similar to Lowe et al (2020). They showed that the total value of the virtual water used to produce one tonne of durum wheat pasta ($212).…”
Section: Discussionsupporting
confidence: 86%
“…The total WF is the sum of those three components and refers to the water directly involved in the agricultural processes, while the indirect water, also known as ‘ virtual water’ , represents the water that is embedded in the preparation of the material and energy commodities utilised for the agricultural processes [ 80 ].…”
Section: A Theoretical Approach To Agricultural Water Footprint Accou...mentioning
confidence: 99%
“…It is clear that global freshwater appropriation is an important issue. In spite of that, there is a global debate on whether WF should be a volumetric or an impact-based indicator as CF is [ 80 ]. The debate is rooted on the important need to fully understand and describe the WF purpose, and to determine the most representative unit of measure for water appropriation [ 80 ].…”
Section: A Theoretical Approach To Agricultural Water Footprint Accou...mentioning
confidence: 99%
See 2 more Smart Citations